THE EFFECTIVENESS OF THE WORK OF PT PERKEBUNAN NUSANTARA V IN THE APPLICATIONOF GEOSPATIAL TECHNOLOGY (CASE STUDY OF PTPN SEI PAGAR UNIT) - Citra Kristin Simbolon; Harapan Tua RFS (ADISAM Publisher, 2022)
Work effectiveness shows the ability of a company to achieve the targets that have been set correctly. The achievement of the targets that have been set based on the applicable size and standards reflects that a company has paid attention to its operational effectiveness. As a large company in its field, PTPN V realizes itsposition is in high competition in the industrial era 4.o. For this reason, PTPN V began to use information technology in the form of drones to assist companies in managing their oil palm and rubber lands. This study aims to determine the effectiveness of the work of PT Perkebunan Nusantar V Pekanbaru in the application of information technology as a form of company awareness of technological developments and to be able to follow the flow and be able to compete in the industrial revolution era 4.o. This type of research is a qualitative research using a descriptive approach and the data needed are primary data and secondary data obtained from observations, interviews, and documentation analyzed by researchers so that they get accurate and clear data regarding the work effectiveness of PT Perkebunan Nusantara V Pekanbaru in the application of information technology in the form of drones that function to calculate the number of principal plants, detect geographical conditions of land, check plant health, and of course take pictures of oil palm fields. The effectiveness of PTPN V's work in the application of drones is assessed through indicators of work quality, quantity of work, and time utilization, in which the company experiences effective and significant results despite several inhibiting factors such as weather and drone motors.